Access to and benefit sharing of plant genetic resources: novel field experiences to inform policy - Vernooy, Ronnie; Ruíz, M. (MDPI, 2013)
A number of national and international policy processes are underway to allow for the development of sui generis systems to protect local natural and genetic resources and related knowledge about their management, use and maintenance. Despite agreements reached on paper at international and national levels, such as the Nagoya Protocol on access to genetic resources and the fair and equitable sharing of benefits derived from their use, and the International Treaty on Plant Genetic Resources for Food and Agriculture, progress in implementation has been slow and in many countries, painful. Promising examples from the field could stimulate policy debates and inspire implementation processes. Case studies from China, Cuba, Honduras, Jordan, Nepal, Peru and Syria offer examples of novel access and benefit sharing practices of local and indigenous farming communities. The examples are linked to new partnership configurations of multiple stakeholders interested in supporting these communities. The effective and fair implementation of mechanisms supported by appropriate policies and laws will ultimately be the most important assessment factor of the success of any formal access and benefit sharing regime.